(34x+56y)+(41x-14y)=

Simple and best practice solution for (34x+56y)+(41x-14y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (34x+56y)+(41x-14y)= equation:


Simplifying
(34x + 56y) + (41x + -14y) = 0

Remove parenthesis around (34x + 56y)
34x + 56y + (41x + -14y) = 0

Remove parenthesis around (41x + -14y)
34x + 56y + 41x + -14y = 0

Reorder the terms:
34x + 41x + 56y + -14y = 0

Combine like terms: 34x + 41x = 75x
75x + 56y + -14y = 0

Combine like terms: 56y + -14y = 42y
75x + 42y = 0

Solving
75x + 42y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42y' to each side of the equation.
75x + 42y + -42y = 0 + -42y

Combine like terms: 42y + -42y = 0
75x + 0 = 0 + -42y
75x = 0 + -42y
Remove the zero:
75x = -42y

Divide each side by '75'.
x = -0.56y

Simplifying
x = -0.56y

See similar equations:

| Z-4-4z=1 | | A(10)=-4+(10-1)(5) | | 4(7-3a)=33 | | a(a+1)=552 | | 3m(4m+1)=12(m^2-8) | | x-2y=300 | | 27-6x=57 | | Z-2-4z=1 | | (-2x^4)(5x^3)= | | (36x+55y)+(-16x+48y)= | | -82+5-22-4+52= | | 4x^2+6x-4x^2= | | (1-x)*ln(9)=(2*x+9)*ln(3) | | -10+4x=-7 | | 3x+30+2x-10+x-6+x-4=360 | | m=-1/10,(-9,0) | | (16x+6y)+(46x+35y)= | | 5z^2-5z=0 | | 2x-3(x-4)=5(x-1)-1 | | (2x+5)(x-5)-7=0 | | X+45+76=x+43 | | Y-6+2=2y-0 | | x^2+y^2+z^2+9x-2y+8z+23=0 | | 6=z+y | | 9x-(x-8)= | | (45x+58y)+(46x-22y)= | | x-7-4x=28 | | 2d+4+6=-18 | | 2a+a=552 | | 2x-(-16)=44 | | X+45+x+43=76 | | 3=16-4x |

Equations solver categories